COVID-19 and Painful Temporomandibular Disorders: what does the dentist need to know? - Jean Soares MIRANDA; Letícia Ladeira BONATO; Ricardo de Souza TESCH (Faculdade São Leopoldo Mandic, 2021)
ABSTRACT COVID-19 outbreak may lead to major impacts in applied oral sciences. Remarkably, it could be expected that factors associated to pandemic may lead to a greater risk of developing, worsening and perpetuating TMD and its associated risk factors. This non systematic literature review aims to discuss how the COVID-19 pandemic can influence the emergence, maintenance or worsening of TMD worldwide. During epidemics: the number of people whose mental health is affected tends to be greater than the number affected by the infection, and fear increases anxiety and stress levels in healthy individuals; chronic pain patients probably not receipt important treatments; overuse of medications becomes frequent; there are manifestation of unconscious oral parafunctional habits and poor sleep quality. All these facts represent risk factors common to TMD. Dentists should be aware of these issues and adapt their practices to properly diagnose and treat these patients within a multifactorial approach, increasing the quality of life of these individuals.